Genome-wide identification of the CclKNOX gene family and functional characterization of CclKNOX3 and CclKNOX5 in citrus shoot development - Zeng, Ren-Fang; Gan, Zhi-Meng; Hu, Si-Fan; Fu, Li-Ming; Gong, Zan; Hu, Chun-Gen; Zhang, Jin-Zhi (Scientia horticulturae, 2024)
KNOTTED1-LIKE HOMEOBOX (KNOX) genes are a relatively conserved gene family in plants, and have important regulatory functions in the morphological development of plants. In this study, a total of 9 KNOX proteins were found from citrus and divided into two classes, Class I and Class II. Subsequently, their gene structures, protein characteristics and sequence features were analyzed. Spatial expression analysis showed that most of the genes exhibited a constitutive expression pattern in different tissues of Citrus clementina. Interestingly, the expression pattern of CclKNOX3 was different from other Class I members, as it was mainly expressed in stems, lateral buds and shoot tips. Overexpression of CclKNOX3 led to strong differentiation of shoot apical meristem and curled leaves in transgenic tobacco and lemon. In addition, CclKNOX3 was found to interact with CclKNOX5, localized in the nucleus and have transcriptional inhibitory activity. Further transgenic analysis found that 35S:CclKNOX5 transgenic tobacco showed similar phenotype with 35S:CclKNOX3. Furthermore, yeast one hybrid and luciferase assay confirmed that CclKNOX3 and CclKNOX5 were regulated by CclKNOX4. This study expands our knowledge about the citrus KNOX family and provides valuable informations for future studies on shoot developmental regulation.